O FUNDEB na prática: uma análise jurídica dos desafios para a implementação de políticas públicas no Brasil - Nunes, Alynne Nayara Ferreira (2016)
This thesis examines the legal structure (departing point) of the Primary and Secondary Education Maintenance and Development Fund (Fundo de Manutenção e Desenvolvimento da Educação Básica e de Valorização dos Profissionais da Educação - FUNDEB), a Federal Government policy to fund and improve education (arrival point). The theoretical framework is that offered by the Law and Development literature, which highlights the importance of institutional arrangements for development (SCHAPIRO e TRUBEK, 2012) as well as Bucci´s studies on public policies (BUCCI, 2006a, 2006b, 2013, 2015) and Sen’s analysis of development (SEN, 2000). Decisions by the Superior Tribunal de Justiça (STJ) and Supremo Tribunal Federal (STF), were examined to assess how the legal design was implemented in practice. Special emphasis is given to decisions on deadlines for transfer of funds and to the issue of teachers’ wages. The analysis suggests that courts granted the Federal government greater discretionary powers than those established by the original design, which may contribute to frustrate, in part or absolutely, the goals aimed by the public policy.